2018
DOI: 10.23968/2500-0055-2018-3-1-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Public Participation in Environmental Impact Assessment (Eia): A Critical Analysis

Abstract: This paper aims at analyzing public participation in Environmental Impact Assessment. It x-rayed the various objectives of public participation in EIA, the prospects and challenges of public participation with a view to making worthwhile recommendation necessary for better public participation in the EIA process.The paper argue that greater attention to public participation during the EIA process leads to better environmental assessment, and thus to the formulation of projects that deliver more social benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…It can enhance decision-making and empower communities in resource development; however, its effectiveness varies depending on the specific project and country (C. Cagnon et al, 1993). Despite the challenges of implementation of public participation in Malaysia's planning system (Marlyana et al,2022), enhanced public participation in the assessments will lead to improved project formulation, resulting in increased social benefits, reduced environmental costs, and greater economic and financial advantages (E. Kanu et al,2018). The implementation of SIA comprises various processes, from screening to auditing phases.…”
Section: Introductionmentioning
confidence: 99%
“…It can enhance decision-making and empower communities in resource development; however, its effectiveness varies depending on the specific project and country (C. Cagnon et al, 1993). Despite the challenges of implementation of public participation in Malaysia's planning system (Marlyana et al,2022), enhanced public participation in the assessments will lead to improved project formulation, resulting in increased social benefits, reduced environmental costs, and greater economic and financial advantages (E. Kanu et al,2018). The implementation of SIA comprises various processes, from screening to auditing phases.…”
Section: Introductionmentioning
confidence: 99%
“…About 37% of Ghana's total exports are made up of minerals, with gold being the most valuable mineral at over 90% of all exports [8]. [11] noted and found that public engagement in environmental impact assessments (EIAs) tends to improve project design, environmental soundness, and social acceptability. The study focused on public participation and EIA in China and Taiwan.…”
Section: Introductionmentioning
confidence: 99%